Exploring the occurrence rate of PMSE‐Es by Digisonde at Tromsø. Issue 2 (13th April 2021) - Li, HaiLong; Ge, ShuCan; Meng, Lin; Wang, MaoYan; Rauf, Abdur; Ullah, Safi
Abstract: Polar mesosphere summer echoes (PMSE) are observed simultaneously with Digisonde and EISCAT VHF radar. The phenomenon of irregular Es layers is called PMSE‐like or PMSE‐Es (Polar Mesosphere Summer Echoes‐Es) and has some relationship with real PMSE. In this paper, the characteristics of irregular Es layers at 80–100 km were observed by Digisonde at Tromsø during 2003–2014 are statistically analyzed with ionograms. The diurnal, day‐to‐day and year‐to‐year variations and discrepancies of occurrence rate between PMSE and PMSE‐Es are compared with the statistical results observed by Esrange MST radar (ESRAD), and the reasons are discussed. The results show that the trends in the occurrence rate of PMSE‐Es are similar to the trends in the occurrence rate of PMSE, but there are some notable differences. The occurrence rate of PMSE‐Es is much lower than the occurrence rate of PMSE. The minimum value of PMSE‐Es appears 1–2 hours earlier than the minimum value of the PMSE occurrence rate, while PMSE‐Es appear earlier than PMSE in the year. In addition, there is a significant positive correlation between the annual average occurrence rates of PMSE and PMSE‐Es. PMSE‐Es is a relatively important occurrence in the polar mesopause. Analysis of its characteristics can provide new ideas and methods for studying the formation mechanism of PMSE. Key Points: PMSE occur much more than PMSE†Es. The diurnal, day†to†day and year†to†year variations of PMSE†Es and PMSE are similar. The correlation between the year†to†year variation of PMSE OR and PMSE†Es OR is positive.